Delhi-Meerut riots : analysis, compilation, and documentation - Engineer, Asgharali, 1940- (Delhi : Ajanta Publications (India) : Distributors, Ajanta Books International, 1988)
On the communal riots in Meerut and Delhi in May 1987
Includes bibliographical references
Koleksi Sumbangan : Dr. Syed Husin Ali
Keywords: Riots -- India -- Meerut; Riots -- India -- Delhi; Communalism -- India -- Meerut; Communalism -- India -- Delhi